Industrial machinery repair best maintenance practices pocket guide - Smith, Ricky; Mobley, Keith (Amsterdam ; Boston, MA : Butterworth-Heinemann, 2003)
Industrial Machinery Repair provides a practical reference for practicing plant engineers, maintenance supervisors, physical plant supervisors and mechanical maintenance technicians. It focuses on the skills needed to select, install and maintain electro-mechanical equipment in a typical industrial plant or facility. The authors focuses on "Best Maintenance Repair Practices" necessary for maintenance personnel to keep equipment operating at peak reliability and companies functioning more profitably through reduced maintenance costs and increased productivity and capacity. A number of surveys conducted in industries throughout the United States have found that 70% of equipment failures are self-induced. If the principles and techniques in this book are followed, it will result in a serious reduction in "self induced failures". In the pocketbook format, this reference material can be directly used on the plant floor to aid in effectively performing day-to-day duties. Data is presented in a concise, easily understandable format to facilitate use in the adverse conditions associated with the plant floor. Each subject is reduced to it simplest terms so that it will be suitable for the broadest range of users. Since this book is not specific to any one type of industrial plant and is useful in any type of facility. The new standard reference book for industrial and mechanical trades Accessible pocketbook format facilitates on-the-job use Suitable for all types of plant facilities.
Introduction : Why use best maintenance repair practices? -- Fundamental requirements of effective preventive/predictive maintenance -- Maintenance skills assessment -- Safety first, safety always -- Rotor balancing -- Bearings -- Chain drives -- Compressors -- Control valves -- Conveyors -- Couplings -- Dust collectors -- Fans, blowers, and fluidizers -- Gears and gearboxes -- Hydraulics -- Lubrication -- Machinery installation -- Mixers and agitators -- Packing and seals -- Precision measurement -- Pumps -- Steam traps -- V-belt drives -- Maintenance welding -- Appendix A: Written assessment answers.
Keywords: MAchinery -- Maintenance and repair; Industrial equipment -- Maintenance and repair; Electronic books